2009
DOI: 10.2134/jeq2008.0412
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Odor and Odorant Emissions from Slurry Stores by Means of Straw Covers

Abstract: Swine (Sus scrofa) slurry stored in open storages is a source of airborne contaminants. A customary practice for ammonia and odor control consists of covering the surface of the slurry with fl oating materials, such as straw. Although straw covers have been proven to generally reduce gaseous emissions, more knowledge is needed regarding how age, moisture content, and microbiological development of the straw cover aff ect the emissions of odor and odorants to develop recommendations for the practical use of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…3) restricting H 2 S emissions (Park et al, 2006b; Petersen et al, 2013). In fact, surface barriers have been shown to significantly reduce H 2 S emissions in lagoons and in laboratory studies (Zahn et al, 2001; Lee et al, 2007; Regmi et al, 2007; Blanes‐Vidal et al, 2009b). …”
Section: Resultsmentioning
confidence: 99%
“…3) restricting H 2 S emissions (Park et al, 2006b; Petersen et al, 2013). In fact, surface barriers have been shown to significantly reduce H 2 S emissions in lagoons and in laboratory studies (Zahn et al, 2001; Lee et al, 2007; Regmi et al, 2007; Blanes‐Vidal et al, 2009b). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, microbial populations in slurry surface crust, absent in the experiment but oft en present in practice, may convert odor compounds into nonodorous compounds. Blanes-Vidal et al (2009) found that aged straw covers reduced emissions of DMS by 81%, whereas no eff ect was found for H 2 S.…”
Section: Odorant Contributionmentioning
confidence: 93%
“…Agriculture is a second potential source (11)(12)(13)(14)(15)(24)(25)(26). It was reported in previous studies that both NH 3 and OSC emissions are associated with livestock activities and that their concentrations were correlated (27,28). Because emission flux measurements were not possible at the time for OSCs, we chose to estimate fluxes of OSCs from agricultural activities in the SoCAB by simultaneously measuring OSC and NH 3 ambient concentrations adjacent to a cattle feedlot in Chino, California (SI Appendix, sections 1 and 2) before dawn to avoid photochemistry.…”
Section: Significancementioning
confidence: 99%